Fracture non-union epidemiology and treatment. (January 2016) - Nandra, Rajpal; Grover, Liam; Porter, Keith
Fracture non-union remains a clinical problem despite advances in the understanding of basic science and technology. Each fracture has a unique personality as does the patient suffering the injury. Thus, each case must be treated on an individual basis. This article defines the problem of fracture non-union and reports recent epidemiological studies. We discuss relevant risk factors and methods for assessing patients who have a tendency toward fracture non-union. There are many treatment options for patients with non-union, where a number of these modalities are still under review. We discuss current evidence with the use of bone morphogenic protein, platelet-rich plasma and low-intensity pulsed ultrasound to augment the treatment of fracture non-union.